2009
DOI: 10.1002/pssc.200880621
|View full text |Cite
|
Sign up to set email alerts
|

Growth of 3C‐SiC nanowires on nickel coated Si(100) substrate using dichloromethylvinylsilane and diethylmethylsilane by MOCVD method

Abstract: We have grown 3C‐SiC nanowires on nickel coated Si(100) substrates using single source precursors by thermal metal‐organic chemical vapor deposition (MOCVD) method. Dichloromethylvinylsilane (CH2CHSi(CH3)Cl2) and diethylmethylsilane (CH3SiH(C2H5)2) were used as a single precursor without any carrier and bubbler gas. 3C‐SiC nanowires with 40 ∼ 100 nm diameter could grow on substrates at temperature as low as 900 °C. XRD pattern showed that SiC nano‐wires were cubic silicon carbide. TEM analysis showed that an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…It can be observed that the CA increased as the growth temperature and time increased and reached the optimum value of ∼160° for the samples grown at 1200 °C for 1 h. As the formation of SiC takes place via an endothermic reaction, increasing the growth temperature as well as the growth time causes the length as well as the density of 3C-SiC NRs to increase. Best results were observed for the Ni thin-film catalyst as it is a good catalyst for the growth of SiC 1D nanostructures , compared to other metal catalysts such as Cu and Ti.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the CA increased as the growth temperature and time increased and reached the optimum value of ∼160° for the samples grown at 1200 °C for 1 h. As the formation of SiC takes place via an endothermic reaction, increasing the growth temperature as well as the growth time causes the length as well as the density of 3C-SiC NRs to increase. Best results were observed for the Ni thin-film catalyst as it is a good catalyst for the growth of SiC 1D nanostructures , compared to other metal catalysts such as Cu and Ti.…”
Section: Resultsmentioning
confidence: 99%
“…Till date, the growth of various 1D 3C-SiC nanostructures such as nanowires (NWs), nanorods (NRs), nanowhiskers, nanobelts, nanoneedles, core–shell NWs, and nanotubes has been reported. The catalytic growth of 1D 3C-SiC nanostructures via vapor–liquid–solid (VLS) mechanism has been mainly achieved by using transition metals especially nickel (Ni) and iron (Fe). Some people have also used gold (Au) as a catalyst. , …”
Section: Introductionmentioning
confidence: 99%
“…Films were synthesized using diethylmethylsilane (DEMS) as a single precursor without any carrier or bubbler gas. Use of a single precursor that contain directly bonded Si and C atoms in a ratio of 1:1, and that decomposes at low temperatures may be effective for SiC growth [12]. Si (111) and sapphire (0001) substrates 1.5×1.5 cm in sizde were prepared by chemical cleaning.…”
Section: Methodsmentioning
confidence: 99%
“…They can incorporate along with growing metal matrix. Generally used second phase particles are hard oxides [7][8][9][10] Carbides [11,12] , Nitrides [1] , solid lubricants [13], TiB 2 [14] and others include diamond, Al flakes [15], nano rods, nano tubes and nano wires [16].…”
Section: Introductionmentioning
confidence: 99%